Effect of foliar spraying solution Grow green and Salicylic acid in growth of sour orange seedling ( Citrus aurantium L. ) - Saady Hasan, Jumhoriya (Journal of Kerbala for Agricultural Sciences, 2018)
This experiment was conducted in the Lathhous of the Technical Instituite \ Musaib during 2016 growth season on sour orange seedling, Which included two Factor : First was study the influence spraying (Grow green) in four levels (0 , 3 , 6 and 9) mg.L-1 and the second factor was study the effect of four levels of spraying with Salicylic acid (0, 50 , 100 and 150) mg.L-1 and their interaction on vegetative , root traits , leaves content of chlorophyll , Nitrogen , Phosphor and Potassium. The experiment in complete design of randomize (CRD) was done with three replicates and five Seedling for each treatment we have got the following results : Spraying solution (Grow green) at 9 mg.L-1 gave the highest means of all characters studied and the content of chlorophyll and (N , P , K) in the leaf. Spraying solution (Salicylic acid ) at 150 mg.L-1 caused highest mean of traits studied. Interaction between the treatment 9 mg.L-1 (Grow green ) Sapling with 150 mg.L-1 Salicylic acid gave the highest values of studied